Zooplankton Structure and Potential Food Web Interactions in the Plankton of a Subtropical Chain-of-Lakes - Karl E. Havens (The Scientific World Journal)
This study evaluates the taxonomic and size structure of macro-zooplankton and its potential role in controlling phytoplankton in the Kissimmee Chain-of-Lakes, six shallow interconnected lakes in Florida, U.S. Macro-zooplankton species biomass and standard limnological attributes (temperature, pH, total phosphorus [TP], chlorophyll a [Chl a], and Secchi transparency) were quantified on a bimonthly basis from April 1997 to February 1999. Concentrations of TP ranged from below 50 to over 150 μg l-1. Peak concentrations of particulate P coincided with maximal Chl a, and in one instance a high concentration of soluble reactive P followed. The cladoceran zooplankton was dominated by small species, including Eubosmina tubicen, Ceriodaphnia rigaudi, and Daphnia ambigua. The exotic daphnid, D. lumholtzii, periodically was abundant. The copepods were strongly dominated by Diaptomus dorsalis, a species previously shown to be highly resistant to fish predation. These results, and findings of controlled experiments on a nearby lake with a nearly identical zooplankton species complement, suggest that fish predation may be a major factor structuring the macro-zooplankton assemblage. Zooplankton biomass, on the other hand, may be affected by resource availability. There was a significant positive relationship between average biomass of macro-zooplankton and the average concentration of TP among the six lakes. No such relationship existed between zooplankton biomass and Chl a, suggesting that the predominant food web in these systems may be based on bacteria-plankton, as has been documented in nearby Lake Okeechobee. All of the zooplankton taxa encountered in the Kissimmee Chain-of-Lakes (except Mesocyclops edax) are known bacteria grazers in Florida lakes. Phytoplankton biomass, measured as Chl a, was strongly associated with TP, both within and across lakes. Phytoplankton biomass was not associated with the biomass of zooplankton. These results, when considered in the context of nutrient-addition, zooplankton-exclosure studies on Lake Okeechobee, support the hypothesis that phytoplankton biomass in subtropical lakes is regulated by —bottom-up,“ rather than —top-down“ forces.